A small independent retailer's performance: Influenced by innovative strategic decision-making skills? - Rainer Hensel; Ronald Visser; Anja Overdiek; Ellen Sjoer (Journal of Innovation & Knowledge (JIK), 2021)
The existence of small independent retailers is seriously jeopardised by severe competitive pressure, mainly caused by the sharp rise in online trading, rapidly changing consumer behaviours and the effectiveness of large commercial companies. It is claimed that small retailers should respond to this pressure by designing and implementing innovative business strategies. However, little is known about the specific entrepreneurial qualities and skills needed to design innovative business strategies to cope effectively with these challenging business environments. A structural equation methodology is used to analyse the impact of strategic decision-making skills, originating from the effectuation framework, on a small retailer's success. Three entrepreneurial qualities and skills proved to be significantly related to a small retailer's effectiveness: 1) innovative personal qualities related to creativity, 2) cognitive analytic business skills, and 3) capacities in inspirational networking. However, a specific path seems to exist. Creativity provides the input for the effective application of cognitive analytic business skills, the latter again directly positively influencing a small retailer's performance. This implies that to be effective, innovative personal qualities should be combined with cognitive business skills. Moreover, the final model revealed an indirect positive influence of inspirational networking on a small retailer's performance. Capacities in inspirational networking have a positive impact, in so far as the following two basic conditions are satisfied: 1) frequent social initiative, and 2) intellectual authenticity. Moreover, the effective application of business skills positively influences inspirational networking skills, an insight again underscoring the necessity to combine cognitive analytic skills and social networking abilities.
Keywords: 650; Business knowledge; Effectuation; Entrepreneurial decision-making; Innovation; Small retailers